Hybrid framework for analyzing reinforced concrete skewed and curved bridges with stochastic traffic loads - Chen, Luke, author; Guo, Yanlin, advisor; Mahmoud, Hussam, committee member; Chen, Suren, committee member; Atadero, Rebecca, committee member; Brandl, Alexander, committee member (Colorado State University. Libraries, 2025)
Reinforced concrete (RC) bridge with skewness or curvature geometry is a common alternative design to overcome terrain obstacle or facilitate highway alignments. Irregular bridge geometric configuration results in completely different performances under earthquakes, traffic loading or long-term distress (e.g., corrosion, fatigue) compared to straight bridges. A better understanding of performances of irregular bridges is crucial for their design and maintenance. In current practice, there is lack of systematic understanding of influence of bridge skew angle and curvature on the structural performance. Also, the existing analysis methods adopt oversimplified structural modeling techniques that prevent proper consideration of traffic loads distribution on irregular bridges. In light of these limitations in the existing studies, the objective of this dissertation is to advance the performance analysis methods of RC skewed and curved bridges under more realistic loading conditions. This dissertation proposes a hybrid framework that integrates detailed finite element (FE) modeling with stochastic traffic simulations to realistically assess the performance of RC skewed and curved bridges. The framework begins with seismic fragility analyses of bridge models under varied geometric configurations, identifying how skewness and curvature amplify vulnerability. A parametric study is conducted to investigate how different earthquake and traffic conditions affect the seismic performance of skewed and curved bridges. Then stochastic traffic loads are incorporated to study vehicle-bridge interactions under seismic events. Structural responses derived from these simulations are further utilized to conduct fatigue life assessments, accounting for both traffic-induced stresses and long-term deterioration like rebar corrosion. The proposed approach provides deeper insights into the combined effects of traffic, seismic loading, and fatigue on skewed and curved RC bridges, offering a more reliable basis for design, maintenance and retrofitting for these bridges.
Keywords: fatigue; rebar corrosion; skewed and curved bridge; fragility curves; bridge traffic interaction; seismic